Hematopoietic activity in putative mouse primordial germ cell populations. (May 2015) - Scaldaferri, Maria Lucia; Klinger, Francesca Gioia; Farini, Donatella; Di Carlo, Anna; Carsetti, Rita; Giorda, Ezio; De Felici, Massimo
Highlights: Heterogeneous expression of the GOF-18ΔPE-GFP Oct3/4 transgene in putative PGCs. Putative PGCs express several genes of hematopoietic precursors. A subset of the putative PGCs (Oct3/4-GFP weak CD-34 weak/high ) possesses hematopoietic CFU activity. A subset of putative PGCs is not definitively germline determined. Abstract: In the present paper, starting from the observation of heterogeneous expression of the GOF-18ΔPE-GFP Pou5f1 ( Oct3/4 ) transgene in putative mouse PGC populations settled in the aorta–gonad–mesonephros (AGM) region, we identified various OCT3/4 positive populations showing distinct expression of PGC markers (BLIMP-1, AP, TG-1, STELLA) and co-expressing several proteins (CD-34, CD-41, FLK-1) and genes ( Brachyury, Hox-B4, Scl/Tal-1 and Gata-2 ) of hematopoietic precursors. Moreover, we found that Oct3/4-GFP weak CD-34 weak/high cells possess robust hematopoietic colony forming activity (CFU) in vitro. These data indicate that the cell population usually considered PGCs moving toward the gonadal ridges encompasses a subset of cells co-expressing several germ cell and hematopoietic markers and possessing hematopoietic activity. These results are discussed within of the current model of germline segregation.